Emergence of Carbapenem- and Tigecycline-Resistant Proteus cibarius of Animal Origin - Li, Yan; Wang, Qian; Peng, Kai; Liu, Yuan; Li, Ruichao; Wang, Zhiqiang (Frontiers in Microbiology, 2020)
The emergence of tet(X) and carbapenemase genes in Enterobacterales pose significant challenges to the treatment of infectious diseases. Convergence of these two categories of genes in an individual pathogen would deteriorate the antimicrobial resistance (AMR) crisis furthermore. Here, tigecycline-resistant Enterobacterales strains were isolated and detected with carbapenemase genes, characterized by antimicrobial susceptibility testing, PCR, conjugation assay, whole genome sequencing, and bioinformatics analysis. Three tigecycline-resistant isolates consisting of one plasmid-mediated tet(X4)-bearing Escherichia fergusonii and two chromosomal tet(X6)-bearing Proteus cibarius were recovered from chicken feces. The tet(X4) was located on a conjugative IncX1 plasmid pHNCF11W-tetX4 encoding the identical structure as reported tet(X4)-bearing IncX1 plasmids in Escherichia coli. Among two P. cibarius strains, tet(X6) was located on two similar chromosomal MDR regions with genetic contexts IS26-aac(3)-IVa-aph(4)-Ia-ISEc59-tnpA-tet(X6)-orf-orf-ISCR2-virD2-floR-ISCR2-glmM-sul2 and IS26-aac(3)-IVa-aph(4)-Ia-ISEc59-tnpA-tet(X6)-orf-orf-ISCR2-glmM-sul2. Apart from tet(X6), P. cibarius HNCF44W harbored a novel transposon Tn6450b positive for blaNDM–1 on a conjugative plasmid. This study probed the genomic basis of three tet(X)-bearing, tigecycline-resistant strains, one of which coharbored blaNDM–1 and tet(X6), and identified P. cibarius as the important reservoir of tet(X6) variants. Emergence of P. cibarius encoding both blaNDM–1 and tet(X6) reveals a potential public health risk.